The Effect Of Financial Ratio To Net Income For The Period 2013-2017: (Study At PT. Bank Syariah Mandiri Indonesia) - Alwahidin; Imam Azizuddin (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2020)
This research aims to find out if the financial ratio has a significant positive effect on net profit for the period 2013-2017 at PT. Bank Syariah Mandiri Indonesia. This research uses quantitative methods using time series data on the financial statements of Bank Syariah Mandiri Indonesia period 2013-2017, purposive sampling used as a method of selection of this research sample. The methods used are descriptive statistical analysis, standard assumption tests and multiple linear regression equation tests with SPSS 21, with a significant rate of 5%. Based on the results of this study, it finds that the financial ratio positively does not have a significant effect on the profit of Bank Syariah Mandiri Indonesia from the f test result obtained from f count of 1,384 with a significant value of 0.284>0.05 because the probability is much higher than 0.05 so it can conclude that there is no significant influence on the variable financial ratio to the profit of Bank Syariah Mandiri Indonesia Period 2013-2017.